The Life and Times of Po Chü-i. - Estate, The Arthur Waley (Taylor and Francis, 2013)
First published in 1949. This book gives the biographical background to the many poems of Po Chü-I (A.D 772-846) and traces the connection between his literary career and the disturbed political life of the time. The volume also provides new translations in whole or in part of about a hundred poems by Po Chü-i.